Bioactive versus bare platinum coils for the endovascular treatment of intracranial aneurysms: systematic review and meta-analysis of randomized clinical trials. (10th September 2015) - Broeders, Joris A; Ahmed Ali, Usama; Molyneux, Andrew J; Poncyljusz, Wojciech; Raymond, Jean; White, Phillip M; Steinfort, Brendan
Abstract : Background: Bioactive coils were introduced in 2002 in an attempt to improve aneurysm healing and durability of angiographic results. Evidence demonstrating superior efficacy to justify the routine use of bioactive coils over bare coils is limited. We compared the periprocedural and clinical outcome after bioactive and bare platinum coiling for intracranial aneurysms. Methods: MEDLINE, EMBASE, Cochrane Library, and ISI Web of Knowledge Conference Proceedings Citation Index—Science were searched for randomized clinical trials (RCTs) comparing bioactive and bare coils. The methodological quality was evaluated to assess bias risk. Periprocedural outcomes and mid-term outcomes were compared. Results: Five independent RCTs comparing bioactive (n=1084) and bare coils (n=1084) were identified. Periprocedural outcome was similar for both groups. Bioactive coiling increased the rate of complete aneurysm occlusion (47% vs 40%; RR 1.17 (95% CI 1.05 to 1.31); p=0.006) and reduced the rate of residual aneurysm neck at 10 months compared with bare coiling in the mid-term (26% vs 31%; RR 0.82 (95% CI 0.70 to 0.96); p=0.01). There were no differences in aneurysm recurrence, aneurysm rupture, stroke, neurological death, modified Rankin Scale score and reinterventions. Subgroup analysis for the three RCTs on hydrogel coils demonstrated reduction of residual aneurysms compared with bare coiling (25% vs 34%; RR 0.76 (95% CI 0.58 to 0.99); p=0.04). Conclusions: Bioactive coils ensure a higher rate of medium-term complete aneurysm occlusion while reducing the rate of residual neck aneurysms compared with bare coiling in the mid-term. Hydrogel coils reduce residual aneurysms compared with bare coils. While there is level 1a evidence to show more complete aneurysm occlusion, longer term follow-up is needed to determine if this translates into clinical significance.